Using the Technology Acceptance Model (TAM) in SAP Fiori - Beselga, D.; Alturas, B. (New Knowledge in Information Systems and Technologies. Advances in Intelligent Systems and Computing, 2019)
This article presents a case study that was carried out in two companies that have implemented SAP Fiori. The As-Is and To-Be description of the process in which SAP Fiori was implemented was performed. The advantages and disadvantages of using SAP Fiori were also identified. The Technology Acceptance Model (TAM) has been used in order to understand the aspects that most influence users to consider SAP Fiori as an added value, and how it optimizes the tasks of users. TAM has two variables that will influence the acceptance of a technology, which are: perceived ease of use and perceived utility.